Pencapaian Kinerja Pemasaran pada Usaha Batik di Pekalongan - Laili Savitri Noor; Fatima Tuzzahara Alkaf; Adi Nugroho (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study aims to analyze the marketing of the batik business in Pekalongan. The method utilized is descriptive and verification methods with a quantitative research approach. A sample of 41 respondents participated in this study. The data analysis is descriptive, verification analysis, path analysis method, and path coefficient. This study aims to examine the relationship between relational marketing and strategic innovation on marketing performance with this data analysis. The study results show no significant correlation between marketing relationship to innovation strategy and strategic innovation to marketing performance. In addition, this study also discusses the direct and indirect effects on the model.